Bioorthogonal Photoclick 1,3-Dipolar Cycloaddition Reaction on Protein – A Review Study - Mandal, Pritha (Current Organic Chemistry, 2023)
Click reactions have gained enormous popularity among chemists for their ambient reaction parameters and wide application in various frontier research fields. Photo-initiated click reactions add another dimension of spatiotemporal control which ensures fruitful bioorthogonal reaction. Several cycloaddition reactions, enlisted in the category of ‘photo click’ reactions due to the fast kinetics and ambient reaction conditions, are widely utilized by scientists for bioorthogonal conjugation. In this review, various types of 1,3-dipolar cycloaddition reactions and their applications in the field of protein bioconjugation are discussed.
Keywords: Photoclick reaction